PENGARUH EARNING MANAGEMENT DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA EMITEN MANUFAKTUR DI BURSA EFEK INDONESIA - Rowland Bismark Fernando Pasaribu; Dionysia Kowanda; Dian Kurniawan (Fakultas Bisnis UKDW, 2015)
This study aims to investigate the relationship earnings management and mechanisms of goodcorporate governance (managerial ownership, institutional ownership, public ownership, the auditcommittee, board size, and proportion of independent board) on the disclosure of corporate socialresponsibility on companies listed in Indonesia Stock Exchange period 2009-2013. Analysis techniqueused is multiple linear regression. From the empirical result, the study found that in partialmanagerial ownership, board size, and proportion of independent board significant influence, whilevariable earnings management, public ownership, and the audit committee did not significantly affectthe disclosure of corporate social responsibility.Keywords: Corporate Social Responsibility, Earnings Management, Good Corporate Governance